Collaborative influence of river discharge and marine current on PHC in Jiaozhou Bay. (January 2019) - Yang, Dongfang; Lin, Dong; Zhang, Yuan; Wang, Qi; Li, Haixia
Abstract: Using investigation data on PHC in May and August 1990, this paper analyzed the collaborative influence of river discharge and marine current on the distributions of PHC in Jiaozhou Bay. Results showed that the PHC contents in May 1990 in surface waters in Jiaozhou Bay were 0.018-0.270 mg L −1, compared to 0.020-0.081 mg L −1 in August 1990. Dagu River and Haibo River were the major PHC sources in May 1990, while Haibo River was the major source in August 1990. In May 1990, there was a "clean path" from the bay center to the bay mouth in where PHC contents were relative low. In August 1990, there was a "polluted region" from the estuary of Haibo River to the center of the bay in where PHC contents were relative high. By means of the collaborative influence of river discharge and marine current there are frozen moments of water exchange.